Guanine oxidation signal enhancement in single strand DNA with polyacrylonitrile/polyaniline (PAN/PAni) hybrid nanofibers - Cam, Ezginur; Tanik, Nilay Aladag; Çerkez, İdris; Demirkan, Elif; Aykut, Yakup (Wiley, 2018)
Pure polyacrylonitrile (PAN) and polyacrylonitrile/polyaniline (PAN/PAni) hybrid nanofibers (NFs) were produced via electrospinning and used to monitor guanine oxidation in single strand DNA (ssDNA) by electrochemical methods. Two different methodologies were conducted. First, pre-synthesized PAni was added into electrospinning PAN solution and electrospun into composite PAN/PAni nanofibrous structure on cylindrical pencil graphite (PGE) surface. In the second route, PAN NFs were electrospun on a PGE surfaces and polymerization of PAni was conducted on the surfaces of the as-spun PAN NFs. NFs were kept at -18 degrees C in a refrigerator for several days. ssDNA was immobilized on the prepared NFs and guanine oxidation signals were observed for each system. The results revealed that use of PAN NFs enhanced signal intensity from 0.92 mu A (PGE) to 1.04 mu A (PAN NFs). Addition of PAni to PAN increased signal intensity to 1.23 mu A. When the PAN NF surfaces were coated with PAni, signal enhancement continued to increase up to 4.19 mu A for fourth day and decreased again when PAni-coated NFs were kept at -18 degrees C in the refrigerator. Since the prepared system is fast and cheap, it is promising for application in DNA biosensor devices. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 45567.
Keywords: biomedical applications; electrospinning; manufacturing; membranes; nucleic acids